Pauli testing tool application design - Priska Analya; Ratnadewi Ratnadewi; Ira Adelina; Michael Claudius Poltak Pintu Batu (Jurnal Mantik, 2023)
The Pauli test in the field of psychology is a tool for tests used to measure individual psychological aspects. The series of activities in the Pauli test are carried out to determine the description of cognitive abilities, emotional conditions, attitude tendencies, and things that affect a person's attitude tendencies. The current Pauli test tool is still conventional, namely paper and pencil, after the test is carried out, the examiner manually analyzes the results of the respondent's activities. This requires a long time and the possibility of human error is large, therefore in our research a software application was designed that can replace conventional methods. The software is made using Visual Basic.NET. The design of the Pauli test software application is made similar to the existing conventional tools. The results obtained from the Pauli test software application are very helpful for psychologist examiners. The final results can be more easily obtained and the time required is more effective, because it is immediately obtained after the test takes place